(untitled) (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2022)
Muslimah clothing is faced with the challenges of developing fashion trends that are developing in this millennial era. This paper intends to understand and explain how the findings of adaptation of Muslim clothing occurred in the millennial era. The method used is a survey method as well as library research where this survey method is carried out randomly on Muslim women aged 15-30 years to answer about understanding the adaptation of Muslim clothing that occurs in the millennial era and understanding clothing that is in accordance with Islamic law. The results of this study indicate that Muslim women in the millennial era already understand how to dress in accordance with Islamic rules and recommendations but are still unable to practice or carry out these rules and recommendations. Millennial-era Muslim women still dress according to trends in the environment and have not used clothing in accordance with Islamic rules and recommendations. This research is able to describe the development of Muslim clothing in the millennial era. So that it can measure how well Muslim women understand trends and the Shari’a in dress.